2015
DOI: 10.3892/mco.2015.492
|View full text |Cite
|
Sign up to set email alerts
|

Periosteal chondroma of the distal tibia: Computed tomography and magnetic resonance imaging characteristics and correlation with histological findings

Abstract: Periosteal chondroma is a rare benign hyaline cartilage neoplasm situated on the bone surface. This is the presentation of a unique case of periosteal chondroma arising in the left distal tibial metaphysis of a 25-year-old female patient with a history of antecedent trauma. The physical examination revealed swelling and tenderness in the anterolateral aspect of the left distal lower limb. Plain radiographs revealed a discernible soft tissue lesion with peripheral foci of mineralization. Computed tomography sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…In series of Boriani et al (7), the mean age was 22.15 years with a mean duration of symptoms of 15 months. In other studies, the age at diagnosis ranged between 12-41 years (5,(8)(9)(10)(11)(12).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In series of Boriani et al (7), the mean age was 22.15 years with a mean duration of symptoms of 15 months. In other studies, the age at diagnosis ranged between 12-41 years (5,(8)(9)(10)(11)(12).…”
Section: Discussionmentioning
confidence: 96%
“…Pandey et al (11) observed no recurrence in radial diaphyseal lesion at two years after marginal excision of periosteal chondroma. Nishio et al (12) performed excision in a 25-year-old female with a distal tibial lesion. At four months of follow-up, the patient was satisfied with no signs of recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Histology exhibits hypercellularity, nuclear pleomorphism, and binucleation, potentially leading to a misdiagnosis of chondrosarcoma. [ 8 ]. The preferred treatment is surgical excision with underlying bone curettage [ 3 , 4 ].…”
Section: Discussionmentioning
confidence: 99%